An assessment of the toxicity of polypropylene microplastics in human derived cells - Hwang, Jangsun; Choi, Daheui; Han, Seora; Choi, Jonghoon; Hong, Jinkee (The Science of the total environment, 2019)
Environmental pollution caused by plastic waste is a growing global problem. Discarded plastic products and debris (microplastic particles) in the oceans detrimentally affect marine ecosystems and may impact human. Humans are exposed to plastic debris via the consumption of seafood and drinking water, contact with food packaging, or inhalation of particles. The accumulation of microplastic particles in humans has potential health risks such as cytotoxicity, hypersensitivity, unwanted immune response, and acute response like hemolysis. We investigated the cellular responses of secondary polypropylene microplastics (PP particles) of approximately ~20 μm and 25–200 μm in different condition and size to normal cells, immune cells, blood cells, and murine immune cells by cytokine analysis, ROS assay, polarization assay and proliferation assay. We found that PP particles showed low cytotoxicity effect in size and concentration manner, however, a high concentration, small sized, DMSO method of PP particles stimulated the immune system and enhanced potential hypersensitivity to PP particles via an increase in the levels of cytokines and histamines in PBMCs, Raw 264.7 and HMC-1 cells. [Display omitted] •PP particles are able to induce pro-inflammatory cytokines such as IL-6, TNF alpha and histamine that cause local immune response.•PP particles induce pro-inflammatory cytokines in size-dependent and concentration manner.